Serological survey of Toxoplasma gondii in captive Neotropical felids from Southern Brazil - Ullmann, Leila Sabrina; Silva, Rodrigo Costa da; Moraes, Wanderlei de; Cubas, Zalmir Silvino; Santos, Leonilda Correia dos; Hoffmann, Juliano Leônidas; Moreira, Nei; Guimarães, Ana Marcia Sá; Montaño, Patrícia; Langoni, Hélio [UNESP]; Biondo, Alexander Welker (Elsevier, 2010)
Toxoplasma gondii is the causative intracellular protozoan of toxoplasmosis in human being and animals. Members of the Felidae family are considered the single definitive host for the infection; both wild and domestic cats are able to excrete oocysts in the environment. Wild cats maintained in captivity may serve as source of infection for other clinically susceptible animals in the same environment. The aim of this study was to determine the frequency of T. gondii IgG antibodies in 57 neotropical felids (1 Leopardus geoffroyi; 3 Puma yagouaroundi; 17 Leopardus wiedii; 22 Leopardus tigrinus; and 14 Leopardus pardalis) kept at the Bela Vista Biological Sanctuary, Itaipu Binacional, Southern Brazil, by the modified agglutination test (MAT) using titer 16 as cut-off point. Seropositivity was observed in 38/57 (66.67%; 95% CI 53.66-77.51%) samples, with higher frequency in ocelots (71.43%). Wild-caught felids were three times more likely to be infected when compared to zoo-born animals (P≤ 0.05) and age of wild-caught animals (P= 0.6892; 95% CI. = 0.7528-1.66) was not significant as a risk factor for the infection, the same occurring with zoo-born animals (P= 0.05; 95% CI. = 0.6267-24.052). These results suggest that, despite efforts to control T. gondii infection in zoo facilities, such as individual pens, hygiene monitoring, veterinary care and pre-frozen meat offered as food, non-domestic felids kept in captivity, particularly the wild-caught specimens, may be invariably exposed to infection due to other environmental sources. © 2010 Elsevier B.V.
Keywords: Captive wild cats; Neotropical felids; Toxoplasma gondii; immunoglobulin G antibody; agglutination test; animal care; antibody detection; antibody titer; Brazil; controlled study; Felidae; female; hygiene; Leopardus geoffroyi; Leopardus pardalis; Leopardus tigrinus; Leopardus wiedii; male; morbidity; mortality; Neotropics; nonhuman; parasite identification; Puma yagouaroundi; serology; Agglutination Tests; Animals; Animals, Wild; Animals, Zoo; Antibodies, Protozoan; Chi-Square Distribution; Female; Male; Seroepidemiologic Studies; Toxoplasma; Toxoplasmosis, Animal; Tropical Climate; Animalia; Felis catus; Felis silvestris; Herpailurus yaguarondi; Oncifelis geoffroyi; Protozoa